A systematic review on recent advancements in Abrasive Flow Machining (AFM). (2022) - Singh, Swarn; Kumar, Harish; Kumar, Santosh; Chaitanya, Saurabh
Abstract: Finishing is the prime requirement for the required finish/texture in the manufacturing of various components used in different industries. The conventional machining methods like lapping, grinding, super finishing and polishing are the commonly used processes used for gaining the required finish. A huge amount near about 40% of the total product cost, industries spend to obtain the required finish after machining. To overcome this cost various advanced processes are used. Abrasive Flow Machining (AFM) is the one of the most commonly non-conventional finishing method. The semi solid abrasive medium is used under pressure on the surface for required finish. This article provides a comprehensive overview on types, parameters, abrasive media and applications of AFM.